2009 American Control Conference 2009
DOI: 10.1109/acc.2009.5160248
|View full text |Cite
|
Sign up to set email alerts
|

Robust and chance-constrained optimization under polynomial uncertainty

Abstract: A chance-constrained optimization problem, induced from a robust design problem with polynomial dependence on the uncertainties, is, in general, non-convex and difficult to solve. By introducing a novel concept -the kinship function -an easily computable convex relaxation of this problem is proposed. In particular, optimal polynomial kinship functions, which can be computed a priori and once for all, are introduced and used to bound the probability of constraint violation. Moreover, it is proven that the solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…To avoid this, in line with the results in [8], we adopt an algorithm to compute the so-called upper bound and lower bound polynomial approximations for I(y). Being different from the ordinary polynomial approximations constructed by interpolation, the upper/lower bound polynomial WeB03.5 approximations have to satisfy additional conditions so that the corresponding estimates are greater/less than the "true" probability for any probability measure f .…”
Section: Hard Bounds For Probabilistic Objective Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…To avoid this, in line with the results in [8], we adopt an algorithm to compute the so-called upper bound and lower bound polynomial approximations for I(y). Being different from the ordinary polynomial approximations constructed by interpolation, the upper/lower bound polynomial WeB03.5 approximations have to satisfy additional conditions so that the corresponding estimates are greater/less than the "true" probability for any probability measure f .…”
Section: Hard Bounds For Probabilistic Objective Functionsmentioning
confidence: 99%
“…According to [12], [8], the above two problems can be converted to standard semi-definite programs (SDPs). Hence, given interval [−α, β], weighting function W (y) and degree ̺, the "optimal" polynomial approximations can be easily computed by standard SDP solvers.…”
Section: Hard Bounds For Probabilistic Objective Functionsmentioning
confidence: 99%
“…This method can only be applied to specific uncertainty structures. In ( [9], [10], [11]) convex relaxations of chance constrained problems are presented by introducing the concept of polynomial kinship function to estimate an upper bound on the probability of constraint. It is shown that as the degree of the polynomial kinship function increases, solutions to the relaxed problem converges to a solution of the original problem.…”
Section: A Previous Workmentioning
confidence: 99%
“…Moreover, components of q need to be independent and have computable finite generating functions. In [18,21,22] convex relaxations of chance constrained problems are presented. The concept of polynomial kinship function is used to estimate an upper bound on the probability of constraint violation.…”
mentioning
confidence: 99%